1997
DOI: 10.1136/ard.56.12.709
|View full text |Cite
|
Sign up to set email alerts
|

Pyogenic, tuberculous, and brucellar vertebral osteomyelitis: a descriptive and comparative study of 219 cases

Abstract: Objectives-To describe a large series of patients with vertebral osteomyelitis (VO), and to compare the clinical, biological, radiological, and prognostic features of pyogenic (PVO), tuberculous (TVO), and brucellar vertebral osteomyelitis (BVO). Methods-A retrospective multicentre study, which included 219 adult patients with VO with confirmed aetiology, who were diagnosed between 1983 and 1995 in two tertiary care centres. Of these patients, 105 (48%) had BVO, 72 (33%) PVO, and 42 (19%) TVO. Results-One hund… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

25
232
7
52

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 325 publications
(316 citation statements)
references
References 36 publications
(65 reference statements)
25
232
7
52
Order By: Relevance
“…f. X-ray after one-year follow-up (lateral view) spondylodiscitis. Other authors have reported similar delays [4,10,16,23]. Clearly mortality could be avoided with an earlier diagnosis.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…f. X-ray after one-year follow-up (lateral view) spondylodiscitis. Other authors have reported similar delays [4,10,16,23]. Clearly mortality could be avoided with an earlier diagnosis.…”
Section: Discussionmentioning
confidence: 79%
“…The most frequent place for bacterial colonisation is the spine [23], frequently at the thoracolumbar junction. This situation together with late diagnosis provokes a higher mortality rate [4,15,16]. These patients are also immunocompromised, have advanced age, and suffer very frequently from concurrent diseases such as diabetes mellitus [9].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis is disclosed with history, physical examination, blood tests for brucellosis, and radiological and histopathological means 8 . Positive blood culture is a definite diagnostic tool however proper use of culture techniques, preparation of several specimens and proper timing of culture particularly before administration of antibiotic treatment are the key features increasing the frequency of growth in culture 3,10,13 . Furthermore, culture of surgical or biopsy specimens could give another chance to reveal the presence of Brucella species.…”
Section: Discussionmentioning
confidence: 99%
“…Spinal abscess due to Brucella species should be treated both medically and surgically especially when neuroradiological images point to a severe mass effect on the neural structures. However, medical treatment could be an alternative to surgery in benign soft-tissue lesions in the absence of neurological deterioration 3,13 . Imaging studies for Brucella spondylitis do not give clues about definitive diagnosis 3,12 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation